Advanced Technologies and the Management of Disruptive Supply Chains The Post-COVID Era - Qudrat-Ullah, Hassan; Ali, Syed Imran (Understanding Complex Systems, 2023)
X, 265 p. 33 illus., 22 illus. in color.